Anxiety Disorder in Jordan during the COVID-19 Pandemic: A Cross-Sectional Study - Mari’e, Latifa; Aboghazleh, Refat; Al-Shatanawi, Tariq; Hiasat, Duaa; Damseh, Mohammad; Almomani, Mohammad; Abuanzah, Wa’el; Mugdadi, Duaa; Abualnil, Aseel; Kanaan, Abeer; Al-Omari, Jamal; Khader, Yousef (Jordan Medical Journal, 2024)
Background and Aims: To determine the prevalence of generalized anxiety disorder among university students in Jordan and its relationship with different socio-demographic factors and coronavirus-related anxiety during the COVID-19 pandemic. Materials and Methods: Over a period of four months, a cross-sectional research design was implemented using a Google Forms online survey, which was comprised of questions relating to socio-demographic factors, chronic illnesses, the Generalized Anxiety Disorder 7-item questionnaire, and the Coronavirus Anxiety Scale. The survey was conducted with 470 participants. Results: The prevalence of generalized anxiety disorder was found to be 41.3%, with females (n=155) being approximately four times more susceptible than males (p=0.000). Individuals with chronic medical conditions or those taking chronic medication were found to be at a higher risk of developing generalized anxiety disorder (63%, p=0.007 and 65.7%, p=0.002 respectively). Unexpectedly, participants living alone (n=15, 24.2%) were less likely to experience generalized anxiety disorder (p=0.003) compared to those living with family (n=179, 43.9%). Lastly, compared to the smoker group, generalized anxiety disorder was more common in the non-smokers (33.3% vs 43.8% respectively, p=0.048). Conclusions: Due to the burden of the current pandemic and its correlation with socio-demographic factors and chronic illnesses, the prevalence of generalized anxiety disorder among university students has increased significantly. Therefore, there is a pressing need to raise awareness among healthcare professionals about the prevalence, diagnosis, and management of generalized anxiety disorder.